In vitro Fermentation Reveals Changes in Butyrate Production Dependent on Resistant Starch Source and Microbiome Composition - Teichmann, June; Cockburn, Darrell W. (Frontiers in Microbiology, 2021)
One of the primary benefits associated with dietary resistant starch (RS) is the production of butyrate by the gut microbiome during fermentation of this fiber in the large intestine. The ability to degrade RS is a relatively rare trait among microbes in the gut, seemingly confined to only a few species, none of which are butyrate producing organisms. Thus, production of butyrate during RS fermentation requires a network of interactions between RS degraders and butyrate producers. This is further complicated by the fact that there are multiple types of RS that differ in their structural properties and impacts on the microbiome. Human dietary intervention trials with RS have shown increases in fecal butyrate levels at the population level but with individual to individual differences. This suggests that interindividual differences in microbiome composition dictate butyrate response, but the factors driving this are still unknown. Furthermore, it is unknown whether a lack of increase in butyrate production upon supplementation with one RS is indicative of a lack of butyrate production with any RS. To shed some light on these issues we have undertaken an in vitro fermentation approach in an attempt to mimic RS fermentation in the colon. Fecal samples from 10 individuals were used as the inoculum for fermentation with 10 different starch sources. Butyrate production was heterogeneous across both fecal inocula and starch source, suggesting that a given microbiome is best suited to produce butyrate only from a subset of RS sources that differs between individuals. Interestingly, neither the total amount of RS degraders nor butyrate producers seemed to be limiting for any individual, rather the membership of these sub-populations was more important. While none of the RS degrading organisms were correlated with butyrate levels, Ruminococcus bromii was strongly positively correlated with many of the most important butyrate producers in the gut, though total butyrate production was strongly influenced by factors such as pH and lactate levels. Together these results suggest that the membership of the RS degrader and butyrate producer communities rather than their abundances determine the RS sources that will increase butyrate levels for a given microbiome.